Avaliação da influência da granulometria de um resíduo da siderurgia na geração de radicais via processo oxidativo avançado - Silva, Carlos Eduardo Pinheiro da (2023)
The steel industry is one of the most important industries in the modern world. However, during the process of transforming iron into steel, a large amount of waste and by-products are generated. One of these residues is mill scale, which comes from continuous casting and rolling and consists of approximately 70% of iron oxides. This waste is typically used in Advanced Oxidative Processes (AOPs), particularly in Fenton or Fenton-Type reactions for degrading potentially polluting organic compounds. The present study proposes to evaluate the different sizes of mill scale particles as an activator of hydrogen peroxide in the formation of reactive oxygen species during the decomposition of organic compounds. To achieve this, a granulometric separation of the mill scale was performed, and four different grain sizes were obtained: T1 (<0.25 mm), T2 (0.25 to 0.84 mm), T3 (0.84 to 2.00 mm), and T4 (>2.00 mm). These different grain sizes were characterized using X-ray, scanning electron microscopy (SEM) with EDX, Infrared, Mössbauer, and elemental analysis. By conducting X-ray and Mössbauer analysis, three phases of iron oxides were identified, wustite (FeO), hematite (Fe2O3), and magnetite (Fe3O4), for sizes T1 and T2. As for T3 and T4, only wustite and magnetite were observed. The SEM analysis showed preferentially spherical particles. EDX and infrared results pointed to the presence of CO32- and SiO2 in the mill scale composition. The study uses the different granulometries obtained in the Fenton reaction in a previously optimized condition, which was observed to promote the formation of the hydroxyl radical (•OH) capable of degrading the imidacloprid compound (IMD). For the T1 granulometry, the study observed the lowest degradation of the IMD (approximately 18%). However, the other sizes (T2 to T4) promoted degradations in the range of 62-83%. The study found that the iron leaching into the solution was pH dependent. A higher consumption of H2O2 in the reaction was related to an increase in the content of leached iron, which consequently leads to a greater degradation of the IMD. The study observed good stability of the T1, T2, and T4 residue sizes in the iron leaching, where the total content of leached iron was low, in the range of 0.02-0.50% in relation to the mass of the sample used. However, the T3 granulometry leached a concentration of 26.67±1.91 mg/L of iron, higher than that allowed by CONAMA Resolution nº 430. Among the sizes of mill scale studied, T2 proved to be the most promising for future applications in the degradation of organic pollutants as it required a smaller amount of H2O2, showed less iron leaching, and is the major granulometry in the mill scale sample.